(untitled) (International Journal of Business Innovation, 2022)
The world economy was severely affected by the COVID-19 pandemic. Maintaining operations during a global crisis was extremely difficult for small enterprises, especially in handicraft sectors. Entrepreneurs who do not have crisis management strategies in place, risk having their businesses shut down unexpectedly. Hence, the researchers aimed to understand and analyse the determinants of microenterprises (Handicraft sector) shutdown and exit strategies during the pandemic. This study utilized a descriptive research design, and registered microenterprises in India were purposively selected in the areas of Cavite. The findings of the study revealed that the majority of the microenterprises were sole proprietors that had been in operation for 2 to 5 years. Consequently, the respondents’ most common problems in managing the enterprise were limitations on direct marketing which also involved bill payments, and work-from-home setup, adoption of the online platform. Most of the determinants of problems that led to business failure during the pandemic were obstacles in the realignment of their respective goals owing to the pandemic, difficulties in product innovation, their ability to pay operational expenses, and their failure to react to the changes in the business environment. Exit strategies used by microenterprises included declaring bankruptcy, refinancing, and selling the business to family or friends. Finally, the researchers recommended crisis-sensitive interventions among the small industries (Handicraft sector) entrepreneurs which involve national government provisions of financial safety nets, retooling, and training of pandemic-sensitive enterprise strategies for micro-entrepreneurs, especially in the handicraft sector and also study the impact of lockdown on MSME.